If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72yp + -12y = 0 Solving 72py + -12y = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '12y' to each side of the equation. 72py + -12y + 12y = 0 + 12y Combine like terms: -12y + 12y = 0 72py + 0 = 0 + 12y 72py = 0 + 12y Remove the zero: 72py = 12y Divide each side by '72y'. p = 0.1666666667 Simplifying p = 0.1666666667
| 5x+500=150 | | -9=3+5a-7 | | -4.9x^2+7.4x+10.9=0 | | 190=7x-13+2x+2+4x+9 | | 5y+13+5-3y=m | | 4(2y-4)=2(y-13) | | 60-(3c+4)=4c+24+c | | 14-6x= | | -4.9x^2+7.4t+10.9=0 | | Lne^2=6 | | 4+5(3x-x)=4(8+2x) | | 2(-2n+5)=4-6n | | 7.36=-0.8(2x-1.2) | | 2(3+3x)=78 | | -9+6x=-3[3-2x] | | -13=m+3-8 | | 10x+20x=12x | | 4p+3=-13 | | -9=-9+x/7 | | (Z+4)and(z-6)=0 | | 5d-d-2d+8=0 | | 4y+8=2b | | 5(1-2n)-6n=37-8n | | (4w-3x)(2w+7x+5)= | | 3/4x+6=9-1/4x | | -2x+-2=4 | | 6cm+w=8cm | | d-18=8 | | 8x+10=-30 | | -3=n/10-4 | | -9v=3 | | -6=-2(h-9) |